Proceedings of the 2018 Conference on Empirical Methods in Natural Language Processing 2018
DOI: 10.18653/v1/d18-1162
|View full text |Cite
|
Sign up to set email alerts
|

Constituent Parsing as Sequence Labeling

Abstract: We introduce a method to reduce constituent parsing to sequence labeling. For each word w t , it generates a label that encodes: (1) the number of ancestors in the tree that the words w t and w t+1 have in common, and (2) the nonterminal symbol at the lowest common ancestor. We first prove that the proposed encoding function is injective for any tree without unary branches. In practice, the approach is made extensible to all constituency trees by collapsing unary branches. We then use the PTB and CTB treebanks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 27 publications
(35 reference statements)
0
46
0
Order By: Relevance
“…Recent research has shown that constituency parsing can be reduced to sequence tagging, a structured prediction problem where for each input token a single label output is generated [7]. To do so, the syntactic trees need to be linearized through an encoding method, as shown in Figure 1a.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has shown that constituency parsing can be reduced to sequence tagging, a structured prediction problem where for each input token a single label output is generated [7]. To do so, the syntactic trees need to be linearized through an encoding method, as shown in Figure 1a.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the closest work to ours is the reduction proposed by Gómez-Rodríguez and Vilares (2018), who cast continuous constituent parsing as sequence labeling. 3 In the next sections we build on top of their work and: (i) analyze why their approach cannot handle discontinuous phrases, (ii) extend it to handle such phenomena, and (iii) train functional sequence labeling discontinuous parsers.…”
Section: Related Workmentioning
confidence: 99%
“…Related to these research aspects, this work explores the feasibility of discontinuous parsing under the sequence labeling paradigm, inspired by Gómez-Rodríguez and Vilares (2018)'s work on fast and simple continuous constituent parsing. We will focus on tackling the limitations of their encoding functions when it comes to analyzing discontinuous structures, and include an empirical comparison against existing parsers.…”
Section: Introductionmentioning
confidence: 99%
“…Rei [28] considers that these patterns are useful for improving accuracy on sequence labeling tasks. Strzyz et al [32] use sequence labeling for constituency [11] and dependency parsing [33] combined with multi-task learning to learn across syntactic representations. They show that adding a parsing paradigm as an auxiliary loss consistently improves the performance on the other paradigm.…”
Section: Sequence Labelingmentioning
confidence: 99%